Pengelolaan arsip di detik Sumatera Selatan - Reni Mustika (UIN Sumatera Utara, 2018)
This article discusses how to manage archives in Seconds South Sumatra, therefore the processing of archives is needed. The archive processing in this secs does not have a special unit in processing because the archive is managed under the editorial secretary, for the storage of the archive in South Sumatra is kept by date on the issuance of the archive and the archive in Seconds of South Sumatra is stored in Data Base and Manual Print. The obstacles faced by Seconds South Sumatra in managing the archive of human resources that are not educational background archives, so in penglolaannya less adequate. Keywords: archive management, mass media archive